A Framework to Assess the Impact of Employee Perceived Equality on Contextual Performance and Mediating Role of Affective Commitment to Enhance and Sustain Positive Work Behavior - Ritika Dongrey; Varsha Rokade (Discrete Dynamics in Nature and Society)
Different employees working in a similar organization may have a different experience-based perception of workforce diversity and management. When employees perceive discrimination, it adversely affects them psychologically and negatively affects their behavior, while perceiving equality reinforces a positive mindset towards other members and management, resulting in healthy work culture. This study investigates the association between perceived equality, affective commitment, and contextual performance. Further, the differences in perception of various genders were examined. The data were collected from (n = 385) employees working in various private organizations in India and were analyzed using the structural equation modeling (SEM) and analysis of variance (ANOVA). The study’s novelty is that, unlike prior research, the study indicated a significant inverse relationship between perceived equality and contextual performance. Moreover, affective commitment mediated the positive relationship between perceived equality and contextual performance. Perceived equality showed a significant positive relationship with affective commitment. Unlike previous research, the analysis of variance demonstrated that both males and females indicated no significant differences regarding contextual performance. Thus, the current research provides a comprehensive model to assess the psychological and behavioral effect of organizational practices related to equal opportunities and representation to diverse employees.